1995
DOI: 10.1007/bf00017673
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 and temperature effects on soil carbon and nitrogen cycling in ryegrass/white clover turves of an Endoaquept soil

Abstract: Effects of elevated CO2 (700/.tL L -l) and a control (350/tL L -I CO2) on the productivity of a 3-year-old ryegrass/white clover pasture, and on soil biochemical properties, were investigated with turves of a Typic Endoaquept soil in growth chambers. Temperature treatments corresponding to average winter, spring, and summer conditions in the field were applied consecutively to all of the turves. An additional treatment, at 700/IL L-i CO2 and a temperature 6°C higher throughout than in the other treatments, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 42 publications
4
33
1
1
Order By: Relevance
“…This effect was similar to results reported by Billes et al (1993), dry weight was stimulated more (in a range of + 44 to + 143%) than shoot dry weight (a range of -2 to + 23%). A similar observation in ryegrass was reported by Ross et al (1995), who found an increase of about 7% and 50% of herbage yield and roots, respectively and by Schapendonk et al (1996) who found increases of 23% and 86%, respectively, in ryegrass swards. For trees, Rouhier et al (1994) found a nonsignificant increase in the fine roots of sweet chestnuts, but not in the aboveground parts.…”
Section: Hypothesis 2 -A Shift Occurs In the Carbon Distribution Withsupporting
confidence: 66%
“…This effect was similar to results reported by Billes et al (1993), dry weight was stimulated more (in a range of + 44 to + 143%) than shoot dry weight (a range of -2 to + 23%). A similar observation in ryegrass was reported by Ross et al (1995), who found an increase of about 7% and 50% of herbage yield and roots, respectively and by Schapendonk et al (1996) who found increases of 23% and 86%, respectively, in ryegrass swards. For trees, Rouhier et al (1994) found a nonsignificant increase in the fine roots of sweet chestnuts, but not in the aboveground parts.…”
Section: Hypothesis 2 -A Shift Occurs In the Carbon Distribution Withsupporting
confidence: 66%
“…Newton et al (1994) and Ross et al (1995), working with turves ofTrifolium repens and Lolium perenne, found that elevated [CO2] differentially promoted the growth of nodulating T. repens. On the other hand, preliminary results reported by Rrtzel et al (1995) suggest no differential responses of nodulating legumes to elevated [CO2] in calcareous grasslands, as compared with non-nodulating plants.…”
Section: Elevated [C02] May Tip the Balance Between Symbiotic And Nonmentioning
confidence: 99%
“…Root biomass is often reported to be enhanced by elevated temperature, for example, increased up to 65% in Bouteloua gracilis (Morgan et al 1994) and 50% in a grass/clover mixture (Ross et al 1995). Experimental warming significantly increased green aboveground biomass in a tallgrass prairie.…”
Section: Introductionmentioning
confidence: 99%